The Fourth Way A Theory of Knowledge - Grossman, Reinhardt (Indiana University Press, 1990)
Reinhardt Grossmann holds that a realistic ontology in regard to perceptual, physical, and mathematical objects can be combined with an empiricistic theory of knowledge. In the first part of the book he shows that the traditional distinction between primary and secondary qualities leads to idealism, while the common Cartesian conception of knowledge by way of ideas leads to skepticism. In an effort to avoid these twin scourges of modem philosophy, the author argues for the existence of ordinary perceptual objects and explains how we know these objects directly through simple acts of perception. The second part of the book is concerned with the way in which we know what is in our minds. Grossmann maintains that this kind of knowledge is just as fallible as perception. In the third part the author concludes that logic, arithmetic, and set theory concern matters of fact and that we discover these facts through empirical knowledge.